1967
DOI: 10.1139/v67-228
|View full text |Cite
|
Sign up to set email alerts
|

Use of ionic bombardment to increase the conductivity of metallized thin plastic films for making source mounts

Abstract: A study was made of the conductivity of thin flexible collodion films metallized either with gold (99.95%) or with gold -18% palladium alloy and the results obtained were compared with the conductivity of VYNS (a polyvinylchloride-acetate copolymer) films coated with the same metals. For both types of films the conductivity is better with the alloy, especially for VYNS. VYNS films coated with gold or the alloy show better conductivity than collodion coated with either metal. However, ionic bombardment of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1970
1970
1972
1972

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The thickness of the SiO layer is calculated from the weight of SiO evaporated from the crucible and the geometry of the evaporating system. 3 We have found that the uniformity and the homogeneity of radioactive sources prepared by air evaporation of the radioactive solutions on SiO deposits 100-300 A thick is greatly improved. For instance the self-absorption of the low energy beta of 63Ni in sources prepared by this technique was only 8%-10% as compared to the values of 30%-70% obtained by other methods commonly used in this field.…”
Section: The Review Of Scientific Instrumentsmentioning
confidence: 95%
See 1 more Smart Citation
“…The thickness of the SiO layer is calculated from the weight of SiO evaporated from the crucible and the geometry of the evaporating system. 3 We have found that the uniformity and the homogeneity of radioactive sources prepared by air evaporation of the radioactive solutions on SiO deposits 100-300 A thick is greatly improved. For instance the self-absorption of the low energy beta of 63Ni in sources prepared by this technique was only 8%-10% as compared to the values of 30%-70% obtained by other methods commonly used in this field.…”
Section: The Review Of Scientific Instrumentsmentioning
confidence: 95%
“…1 at a distance of about 12 cm from the crucible. It is a common type of mount used in the preparation of radioactive sources in 411" (3 counting. The evaporation of SiO was done with a "Speedivac" model 6E2 coating unit made by Edwards High Vacuum Ltd.…”
Section: The Review Of Scientific Instrumentsmentioning
confidence: 99%
“…On doit s'attendre a ce qu'il en soit ainsi si les pertes sont dues 8 En fait, on peut dire que les pertes, s'il y en a, sont de beaucoup inftrieures 20.5% puisqu'il n'y a pas eu de contamination du systime de dttection durant l'tvaporation; nous sommes portts a croire qu'elles sont nulles.…”
Section: Puppauation Et ~T U D E D'une Sourceunclassified